Association of multiple patient and disease characteristics with the presence and type of pain in chronic pancreatitis. Issue 2 (31st July 2019) - Olesen, Søren S; Kuhlmann, Louise; Novovic, Srdan; Nøjgaard, Camilla; Kalaitzakis, Evangelos; Jensen, Nanna M; Engjom, Trond; Dimcevski, Georg; Waage, Anne; Haas, Stephan L; Vujasinovic, Miroslav; Riauka, Romualdas; et al.
Abstract: Background and Aim: Pain is the primary symptom of chronic pancreatitis (CP) and associates with a number of patient and disease characteristics. However, the complex interrelations of these parameters are incompletely understood, and pain treatment remains unsatisfactory in a large proportion of patients. The aim of this study is to investigate multiple pain risk factors in a large population of CP patients, with a special emphasis on patients' patterns of smoking and alcohol use. Methods: This was a multicenter, cross‐sectional study including 1384 patients with CP. Patient demographics and disease characteristics, as well as current patterns of smoking and alcohol use, were compared for patients with pain ( n = 801) versus without pain ( n = 583). Multivariate logistic regression models were performed to assess the variables associated with the presence and type of pain (constant vs intermittent pain). Results: The mean age of participants was 52.1 ± 14.6 years, and 914 (66%) were men. Active smoking (odds ratio 1.6 [95% confidence interval 1.1–2.2], P = 0.005) and alcohol consumption (odds ratio 1.8 [95% confidence interval 1.1–3.0], P = 0.03) were independently associated with the presence of pain. In addition, patients' age at diagnosis, pancreatic duct pathology, and the presence of pseudocysts, duodenal stenosis, and exocrine pancreatic insufficiency were confirmed as pain risk factors (all P ≤ 0.01). Constant pain, as opposed to intermittent pain, was more frequently reported by smokers ( P = 0.03), while alcohol consumption was associated with intermittent pain ( P = 0.006). Conclusion: Multiple patient and disease characteristics, including patterns of smoking and alcohol consumption, associate with the presence and type of pain in patients with CP.